Les verbes français à préfixe co- - Nkollo, Mikołaj (Neophilologica, 2004)
The present paper deals with morphological, semantic and syntagmatic properties of French verbs with prefix co-. The methodological frame deemed most adequate for their description is “lexical decomposition”. Among these verbs, there is a considerable number of those which designate symmetric relations (they follow the pattern x Ry -> y R x). It is further argued that another common feature of these predicates is a compulsory presence of comitative phrase in their syntactic neighbourhood. After a short glimpse over word-formation problems arising within this class of verbs, the historical mechanisms responsible for the formal discrepancy between co- and the corresponding preposition avec (other Romance languages are more conservative; cf. it. La data del tuo arrivo coincide con quella della mia partenza) are carefully scrutinized. Another step is a semantic description of French verbs with prefixe co-. The solution reached at suggests that the meaning of almost all of them incorporates a semantic constant WITH.